Hypertension - Nadar, Sunil; Lip, Gregory Y. H. ([Oxford] : Oxford University Press, 2015)
The management of hypertension varies considerably from clinician to clinician. This resource is a concise and evidence-based summary of current understanding and practice, including the most up-to-date guidance from national bodies and their recommendations for hypertension care. It covers the different phases of investigation and definitive management, and has been fully updated to include new data on the epidemiology of hypertension and new treatment options, as well as a new chapter on renal denervation in hypertension.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on July 15, 2015).
Keywords: Hypertension